Politics in the family: Nepotism and the hiring decisions of Italian firms - Gagliarducci, Stefano and Manacorda, Marco (American Economic Journal: Applied Economics)
This paper studies the effect of family connections to politicians on individuals' labor market outcomes. Using data for Italy spanning more than three decades on a sample of almost one million individuals plus data on the universe of individuals holding political office, we show that politicians extract significant rents, in terms of private sector jobs, for their family members. We present evidence consistent with the hypothesis that this phenomenon is a form of corruption, i.e., a quid pro quo exchange between firms and politicians, although arguably an inferior substitute for easier-to-detect modes of rent appropriation on the part of politicians. - Reproduced
Keywords: Nepotism, Family connections, Politics, Corruption